ChemInform Abstract: Deep Eutectic Solvent as a Highly Efficient Reaction Media for the One‐Pot Synthesis of Benzo‐Fused Seven‐Membered Heterocycles. Issue 48 (10th November 2016) - Shaabani, Ahmad; Hooshmand, Seyyed Emad; Nazeri, Mohammad Taghi; Afshari, Ronak; Ghasemi, Shima
Abstract: The combination of choline chloride and urea as a deep eutectic solvent is applied to the synthesis of tricyclic 1, 4‐benzoxazepines (IV) and 1, 4‐benzodiazepines (VI).